Linkage Stock Price, Trading Volume Activity, Stock Returns and Trading Frequency on Bid Ask Spread - Alkusani Alkusani; Anita Handayani; Yosi Firda Rahmadani (Universitas Muhammadiyah Gresik, 2020)
The purpose of this study was to to examine the effect of stock prices, trading volume activities, stockreturns and trading frequency of the bid ask spread of LQ45 company. Determination of the studysample consist of 42 companies conducted using purposive sampling method. As for hypothesistesting and research instruments using multiple linear regression analysis SPSS 20.0. Result of thisstudy prove that all of the independent variable does not affect the bid ask spread